Optimization of Salak Fruit Distribution Routes With Vehicle Routing Problem (VRP) Using Clarke And Wright Saving's - Simamora, Hasna Ulpa Ujiah; Rakhmawati, Fibri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The problem in the Romaromi expedition which is addressed to Padangsidimpuan City, South Tapanuli Regency, Marancar District, precisely in Sugi Julu village which produces salak fruit is that the delivery of goods is done manually and irregularly where the goods are sent from the warehouse to the customer, and back to the warehouse, so it will cost a lot of time and also costs. Furthermore, to determine the allocation of consumers among existing routes, the sequence of routes that are able to go to all consumers from the specified route from vehicles that are able to pass all routes. Based on the problem in question, this study was made with a vehicle routing problem using Clarke and Wright savings or saving matrix by completing the calculation of savings measured from the many reductions between distance traveled and time used, involving nodes also making it one of the best route paths based on the greatest savings value, namely the distance traveled from the starting point to the intended end point. From the results obtained in data processing using Clarke and wright savings as many as 14 distribution routes. This shows that the Clarke and wright savings algorithm can minimize distance and also save company expenses.